2017
DOI: 10.4081/hr.2017.7088
|View full text |Cite
|
Sign up to set email alerts
|

Two cases of angioimmunoblastic T-cell lymphoma with concomitant positive serology for acute Epstein-Barr virus infection

Abstract: Angioimmunoblastic T-cell lymphoma (AITL) is a rare type of peripheral T-cell lymphoma. Epstein-Barr virus (EBV) is known to be associated with pathogenesis and histological progression of AITL and the onset of the disease often mimics an infectious process. Here we describe two cases of patients with serology for acute EBV infection at the onset of AITL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…6,11 Few data are available regarding the anti-EBV serology status and clinical outcome. 9,10 Here, although in a small cohort of patients, we show that a triple-positive anti-EBV serology is very frequent (77.7%) at the diagnosis of AITL. This finding does not allow us to differentiate a late primary infection from a viral reactivation; serology prior to the development of lymphoma is not available.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…6,11 Few data are available regarding the anti-EBV serology status and clinical outcome. 9,10 Here, although in a small cohort of patients, we show that a triple-positive anti-EBV serology is very frequent (77.7%) at the diagnosis of AITL. This finding does not allow us to differentiate a late primary infection from a viral reactivation; serology prior to the development of lymphoma is not available.…”
Section: Discussionmentioning
confidence: 53%
“…In the literature, only 3 AITL cases with positive serology for anti-EBV IgM at disease onset are described. 9,10 In this study, we analyze EBV serology retrospectively in a series of patients with AITL at disease onset.…”
Section: Introductionmentioning
confidence: 99%
“…This study was carried out on an EBV-seropositive patient who, after chemotherapy and allo-SCT to treat a CD4 + AITL, suffered from relapse and simultaneous increase of EBV load, probably connected to reemergence of malignancy. High EBV viremia is associated with AITL progression, which suggests a possible role in its pathogenesis [2] and increased aggressiveness [4]. Despite DLI and Rituximab treatment, adoptive transfer of T cells enriched for EBV epitopes was provided due to increasing levels of EBV viral DNA in blood and lack of EBV peptide-MHC multimer-binding T cells for six known HLArelevant epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Our patient is the fourth reported, and as far as we can tell, the first reported presenting with a gastric mass. Several theories exist regarding the role of EBV in the pathogenesis of AITL 1,3,4 . A large prospective study showed that circulating EBV DNA is tied to circulating AITL cells.…”
Section: Discussion/conclusionmentioning
confidence: 99%